A Mild PPTS-Catalyzed Acetalization of α,β-Unsaturated Aldehydes: The First Single-Step Protocol towards Benzylic Acetals - Böse, Dietrich; Lübcke, Marvin; Pietruszka, Jörg (Synthesis, 2013)
A mild and convenient procedure for the synthesis of highly sensitive benzylic acetals from α,β-unsaturated aldehydes and the corresponding benzylic alcohols is reported. The new method provides a single-step access to these compounds for the first time. The applications of pyridinium p-toluenesulfonate (PPTS) as a very mild Brønsted acid catalyst and 5 Å molecular sieves (MS) as the dehydrating agent were found to be essential. Furthermore, an application of the acetals in the synthesis of 1-functionalized dienes is exemplified.
Keywords: acetals; zeolites; molecular sieves; dienes; aldehydes